Factors affecting Government Audit Performance: Organizational Commitment, Understanding of Good Governance and Role Ambiguity - Rita Tri Damayantie; Cris Kuntadi (Dinasti International Journal of Education Management And Social Science, 2023)
This article discusses the factors that influence Government Audit Performance as the dependent variable. Variable Organizational Commitment, Understanding of Good Governance and Role Ambiguity as independent variables that affect it. This study is a literature review which describes the influence organizational commitment, good governance and role ambiguity on government audit performance. This article is a study in applied administration to increase influence literacy among variables for further research purposes. The results of the literature review are organizational commitment, understanding of good governance and role ambiguity effect on government audit performance.